The control system of synchronous movement of the gantry crane supports; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Odnokopylov I. G. Ivan Georgievich; Gneushev V. V. Vitaly Viktorovich; Galtseva (Gal’tseva) O. V. Olga Valerievna; Natalinova N. M. Nataliya Mikhailovna; Li J.; Serebryakov D. I. (2017, 2017)
Title screen